Особливості захисту прав людини та громадянина органами конституційної юстиції в Україні й Республіці Польща - Шевчук, Ірина Миколаївна; Shevchuk, Iryna M. (Міжнародний гуманітарний університет, 2014)
У статті досліджено правове регулювання захисту конституційних прав і свобод людини й громадянина органами конституційної юстиції в Україні й Республіці Польща. З’ясовано особливості здійснення Конституційним Судом України й Конституційним Трибуналом Республіки Польща повноважень, спрямованих на захист та забезпечення прав і свобод людини й громадянина. Визначено правовий механізм функціонування конституційної скарги в Республіці Польща. Проаналізовано перспективи впровадження інституту конституційної скарги в Україні з урахуванням польського досвіду.

This article explores the legal regulation of constitutional rights and freedoms of human and citizen by the bodies of constitutional justice in Ukraine and the Republic of Poland. The features of the implementation policy of the Constitutional Court of Ukraine and the Constitutional Tribunal of Poland aimed at protecting and ensuring the rights and freedoms of human and citizen are defined. Legal mechanism of constitutional complaint functioning in the Republic of Poland is defined. The prospects of constitutional complaint introduction in Ukraine that are based on the Polish experience are analyzed.
Features of protection of human and civil rights by the organs of constitutional justice in Ukraine and Republic of Poland
Keywords: Конституційний Суд України; права та свободи людини й громадянина; конституційне звернення; права та свободи людини й громадянина; конституційна скарга; Конституційний Трибунал; Конституція Республіки Польща; Constitutional Court of Ukraine; constitutional appeal; rights and freedoms of human and citizen; constitutional complaint; Constitutional Tribunal; The Constitution of Republic of Poland